2022
DOI: 10.2147/cmar.s363629
|View full text |Cite
|
Sign up to set email alerts
|

A 5`-tRNA Derived Fragment NamedtiRNA-Val-CAC-001 Works as a Suppressor in Gastric Cancer

Abstract: Background Gastric cancer (GC) is a common type of gastrointestinal tumor in the world. Transfer RNA (tRNA) derived fragments (tsRNAs) implicate various cancers, but their roles in GC remain unclear. Our study aimed to investigate the potential biological functions and molecular mechanisms of tsRNAs in GC. Methods Differentially expressed tsRNAs were identified using high-throughput sequencing. The expression levels of tsRNAs were validated in 62 paired GC tissues and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Numerous studies have shown that tsRNAs are related to metastasis, proliferation, cell cycle, and apoptosis (Li et al 2018 ; Sun et al 2018 ; Telonis et al 2019 ). For example, Zheng et al found that high-expressed tiRNA-Val-CAC-001 inhibited the metastasis and proliferation of gastric cancer cells, but promoted apoptosis in GC, and tiRNA-Val-CAC-001 may act as a tumor suppressor and therapeutic target (Zheng et al 2022 ). Although research on tsRNA is still in its infancy, with the advancement of technology and thorough investigation, humans will have a more extensive and in-depth grasp of tsRNA and its biological characteristics and functions in associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that tsRNAs are related to metastasis, proliferation, cell cycle, and apoptosis (Li et al 2018 ; Sun et al 2018 ; Telonis et al 2019 ). For example, Zheng et al found that high-expressed tiRNA-Val-CAC-001 inhibited the metastasis and proliferation of gastric cancer cells, but promoted apoptosis in GC, and tiRNA-Val-CAC-001 may act as a tumor suppressor and therapeutic target (Zheng et al 2022 ). Although research on tsRNA is still in its infancy, with the advancement of technology and thorough investigation, humans will have a more extensive and in-depth grasp of tsRNA and its biological characteristics and functions in associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Through their interaction with proteins or mRNA, inhibition of translation and regulation of gene expression, tRFs play biological roles 23 . It has also been observed that dysregulation of tDRs is associated with several cancers, including PC 24–26 . tRFs are part of tDRs and formed by the processing of tRNA by nucleases such as DICER and angiopoietin under certain conditions 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Using the CCK-8 reagent, the viability of PK15 cells after gallocatechin gallate treatment was determined as previously reported [ 21 ]. PK15 cells were preseeded in 96-well plates at 2 × 10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%